Math-terpieces: The Art Of Problem-Solving - Greg Tang & Greg Paprocki
NEW YORK TIMES bestselling author Greg Tang challenges kids to solve problems creatively while introducing art history. In his most ground-breaking book since THE BEST OF TIMES (Fall 2002), Greg Tang underscores the importance of four basic rules in problem-solving. Keeping an open mind, looking for unusual number combinations, using multiple skills (like subtracting to add) and looking for patterns, will guarantee any child success in math. In MATH-TERPIECES, Tang continues to challenge kids with his innovative approach to math, and uses art history to expand his vision for creative problem-solving.